A 2-pole winding development technique for asynchronous machines with increased number of parallel branches - V.D. Lushchyk (National Technical University "Kharkiv Polytechnic Institute", 2014)
A 2-pole winding development technique is introduced for asynchronous machines with the number of parallel branches in phases increased in 1.5 and 2 times as compared with the number of poles. The technique is confirmed by results of pilot studies.